Brain Derived Neurotrophic Factor Deficiency is Associated with Cognitive Impairment and Elevated Phospholipase A2 Activity in Plasma of Mice. (1st January 2022) - Schmidt, Michaela; Rossetti, Andrea Carlo; Brandwein, Christiane; Riva, Marco Andrea; Gass, Peter; Elsner, Peter; Hesse-Macabata, Jana; Hipler, Uta-Christina; Smesny, Stefan; Milleit, Berko
Highlights: BDNF heterozygous mice display deficits in the T-maze test. There is a quadratic association of PLA2 with performance in the open field test. BDNF deficiency and female sex are associated with elevated plasma PLA2 levels. PLA2 is significantly correlated with adrenal and body weight. Abstract: Decreased levels of Brain-Derived Neurotrophic Factor (BDNF) are a common finding in schizophrenia. Another well-documented protein linked to schizophrenia is intracellular Ca 2+ -independent Phospholipase (PLA2). However, the potential association between PLA2 and BDNF with regard to schizophrenia has yet to be examined. In the present study, male and female BDNF knockout mice, a possible genetic model of schizophrenia, were exposed to prenatal stress and tested in the nest test, open field test and T-maze. Following behavioral tests, whole brain and plasma samples were harvested to measure the activity of PLA2. BDNF knockout mice showed cognitive deficits in the T-maze. Furthermore, there was a quadratic association of PLA2 with performance in the open field test. Moreover, BDNF deficiency and female sex were associated with elevated plasma PLA2 levels. The cognitive impairment of BDNF heterozygous mice as well as their increased PLA2 activity in plasma is consistent with findings in schizophrenia patients. The particular elevation of PLA2 activity in females may partly explain sex differences of clinical symptoms in schizophrenia (e.g. age of onset, severity of symptoms). Additionally, PLA2 was significantly correlated with body and adrenal weight after weaning, whereby the latter emphasizes the possible connection of PLA2 with steroidogenesis.